If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 5y + -3y Combine like terms: 5y + -3y = 2y 11 = 2y Solving 11 = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 11 + -2y = 2y + -2y Combine like terms: 2y + -2y = 0 11 + -2y = 0 Add '-11' to each side of the equation. 11 + -11 + -2y = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -2y = 0 + -11 -2y = 0 + -11 Combine like terms: 0 + -11 = -11 -2y = -11 Divide each side by '-2'. y = 5.5 Simplifying y = 5.5
| -1.1-(-10.1)= | | (6y+8)-(3+5y)=8 | | 400x= | | 15+h=10 | | 3(8)=n(0.08)(300) | | 8x+4=x-14 | | 13x^3-36x=-12x^2 | | 2x-3xm-3x*4=-2m-8 | | 4x-5x-3=0 | | 2x+8y=x-2y | | Y=-5/3-5 | | 2x--2=2 | | 3.4=15.9-5w | | 5x^2+3x=2x(x+6) | | 6p+6=5p+14 | | z+0.9=3.1 | | x(2-12-3m)=-8-2m | | r(1.4+35)=436.60 | | 4x-7=59-7x | | x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 | | (u^4/-2w^2)^2 | | -56=y-49 | | -67=-32n+29 | | 20(b+7)=-20 | | 5b-16=39 | | 76=y/4 | | 2.1x+1.3=-9.2 |